2020
DOI: 10.31018/jans.vi.2279
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic SWOT appraisal of the wicker handicraft entrepreneurship development in Kashmir, India

Abstract: Critical analyses of the perceptions on SWOT (strengths, weaknesses, opportunities and threats) have become a fundamental element of multi-criteria decision making for developing wicker handicraft entrepreneurship. The study examined the effectiveness and prioritization of entrepreneur's perceptions towards SWOT categories and factors and provided insights for developing wicker handicraft entrepreneurship in Pulwama district of Kashmir. Data were collected through structured interviews and focus group discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The findings on the preference in the training methods perceived by the NTFR stakeholders revealed that all the training methods including short duration trainings (1-7 days), medium duration trainings (8)(9)(10)(11)(12)(13)(14)…”
Section: Preference Of Training Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings on the preference in the training methods perceived by the NTFR stakeholders revealed that all the training methods including short duration trainings (1-7 days), medium duration trainings (8)(9)(10)(11)(12)(13)(14)…”
Section: Preference Of Training Methodsmentioning
confidence: 99%
“…"Entrepreneurship in non-timber forest resources (NTFR) is a well-known traditional small-scale forest-based enterprises of rural communities in rural Kashmir" [12]. "Undoubtedly, it is the most widespread and admired entrepreneurship transferred from time immemorial and intensely rooted in local socio-culture" [13]. "The NTFR entrepreneurship on herbal medicines, essential oils, spices and condiments, wild foods (fruits, vegetables, mushrooms, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The export potential of handicrafts from Indonesia has good prospects. The prospect of craft entrepreneurship has a dominant power in developing handicraft businesses (Islam et al, 2020). Entrepreneurship in the form of small and medium enterprises, there are many MSMEs in handicrafts scattered throughout Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…the wicker handicraft entrepreneurship occupy an important ndustrial sector playing a vital role in the economic well-being of the Although, the wicker handicraft entrepreneurship has been recognized as an important option in state's industrial and economic planning but still some instant and sensible policy implications is required to uplift this industry [15,16]. While existing studies by earlier workers [5,[9][10][11][12][13][14][15][16] have widened our knowledge on various aspects of wicker handicraft, the empirical researches on the economic dependence on wicker handicraft entrepreneurship, impacts on income inequality mitigation and determinant factors of entrepreneurship are still essential areas of research to be addressed. Since, the wicker handicraft entrepreneurship remained an integral component of livelihood strategies among the forest fringe communities of Pulwama, J&K, such aforesaid research is urgent.…”
Section: Introductionmentioning
confidence: 99%